Multimodal Language Models in Visual Mathematical and Scientific Reasoning - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 15 peer-reviewed papers addressing the following research question: How do multimodal language models perform on visual mathematical and scientific reasoning v11. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 2.0/10. This report is a machine-generated literature synthesis and does not constitute original research.
Machine-generated literature synthesis.